Rethinking Islamic Pedagogy for Diversity: A Conceptual Analysis of Moderate Islamic Education's Role in Reducing Prejudice in Multicultural Social Settings - Masdar Hilmy; Moh. Dannur; Nur Syarifuddin (Pascasarjana IAI Al-Khairat Pamekasan, 2026)
This conceptual study aims to develop a theoretical framework examining how moderate Islamic pedagogy can reduce prejudice within multicultural societies. Through systematic library research analyzing 127 sources including peer-reviewed journal articles, scholarly books, and policy documents, this study identifies four primary pedagogical mechanisms synthesized into the